Effect of regular precooling on adaptation to training in the heat - Choo, H. C.; Peiffer, J. J.; Pang, J. W.; Tan, F. H.; Aziz, A. R.; Ihsan, M.; Lee, J. K. W.; Abbiss, C. R. (European Journal of Applied Physiology, 2020)
Purpose: This study investigated whether regular precooling would help to maintain day-to-day training intensity and improve 20-km cycling time trial (TT) performed in the heat. Twenty males cycled for 10 day × 60 min at perceived exertion equivalent to 15 in the heat (35 °C, 50% relative humidity), preceded by no cooling (CON, n = 10) or 30-min water immersion at 22 °C (PRECOOL, n = 10). Methods: 19 participants (n = 9 and 10 for CON and PRECOOL, respectively) completed heat stress tests (25-min at 60% VO2peak and 20-km TT) before and after heat acclimation. Results: Changes in mean power output (Delta MPO, P = 0.024) and heart rate (Delta HR, P = 0.029) during heat acclimation were lower for CON (Delta MPO - 2.6 ± 8.1%, Delta HR - 7 ± 7 bpm), compared with PRECOOL (Delta MPO + 2.9 ± 6.6%, Delta HR - 1 ± 8 bpm). HR during constant-paced cycling was decreased from the pre-acclimation test in both groups (P < 0.001). Only PRECOOL demonstrated lower rectal temperature (Tre) during constant-paced cycling (P = 0.002) and lower Tre threshold for sweating (P = 0.042). However, skin perfusion and total sweat output did not change in either CON or PRECOOL (all P > 0.05). MPO (P = 0.016) and finish time (P = 0.013) for the 20-km TT were improved in PRECOOL but did not change in CON (P = 0.052 for MPO, P = 0.140 for finish time). Conclusion: Precooling maintains day-to-day training intensity and does not appear to attenuate adaptation to training in the heat.